Impact of a lingering crisis on the perception of internal communication by employees: A case in the automotive sector - Freitag, Alan (2013)
This article examines internal communication during organizational change driven by a lingering crisis and reports on research conducted among the employees of an automotive industry company. The authors sought support for the thesis that in times of economic downturn, employees tend to appreciate more the very fact of employment as a job satisfaction factor. Concomitantly, it is suggested, employees during an economic slump seek more strongly information on their company’s market situation and financial condition. Although it was not possible to unequivocally verify the first thesis, this research supports the second. When economic crisis hits the industry and job stability is threatened, employees tend to look for information on their company’s situation, number of orders and the corporate strategy because they realize the close correlation between this information and their employment security.